Positive psychology and employee adaptive performance: systematic literature review - Tang, Guihong; Abu Bakar, Raida; Omar, Safiah (Frontiers in Psychology, 2024)
The study explores the relationship between employee adaptive performance research via the prism of positive psychology. With systematic evaluation of 27 studies management journals, individual adaptable performance is investigated in connection to employee positive psychology.This study presents the underpin theories used in analyzing the relationship between positive psychology and employee adaptive performance, the causality and the measurement. This study is trying to map the current knowledge at the nexus of positive psychology and adaptive performance to identify existing gaps and potential for further investigation. Implications of the results are discussed, and directions for future research are presented.